Politicians’ green incentives and external auditing - HOPE, Ole-Kristian (Institutional Knowledge at Singapore Management University, 2024)
This paper examines whether and how politicians’ green incentives affect external auditing. Specifically, we investigate the effects of China’s Green Audit of Outgoing Officials (GAOO) policy, which directly links environmental performance to public officials’ promotions. Employing a DID approach, we observe a significant reduction in audit fees for high-polluting firms after the implementation of GAOO. The decrease is stronger among firms located in regions with departing public officials. We identify two channels driving this trend: (1) Auditors rely on public information generated from intensified governmental efforts, thereby economizing on their efforts (i.e., a substitution effect); (2) High-polluting firms improve their environmental performance, leading to diminished client risk. Additional analyses show that GAOO does not lead to the deterioration in audit quality or the switch to lower-ranked audit firms.